2005
DOI: 10.1021/je050069s
|View full text |Cite
|
Sign up to set email alerts
|

Speeds of Sound, Densities, and Isentropic Compressibilities of 1-Iodohexane at Temperatures from (293.15 to 413.15) K and Pressures up to 200 MPa

Abstract: Experimental speeds of sound and densities are presented for the liquid phase of 1-iodohexane. The measurements were carried out along nine isotherms from (293.15 to 413.15) K at pressures from the saturation condition up to 200 MPa. The speed of sound was measured by a pulse-phase echo ultrasonic device at a frequency of (1 to 5) MHz with an uncertainty of ±0.2%. The density was measured by an acoustic piezometer with an uncertainty of ±0.3%. The experimental results have been used to calculate the isentropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…This time we report experimental and interpolated data on thermophysical properties of 1-chloroheptane and 1-iodoheptane at 216.08 ≤ T ≤ 423.1 K and 0.1 ≤ P ≤ 196.1 MPa. The current analysis covers also the previously published results for 1-iodohexane, 4 1chlorohexane, 5 and 1-chloropropane 6 in similar P−T ranges, along with the volumetric properties of 1-alkyl bromides 7,8 and the eminent 9 data 10−13 of Percy Williams Bridgman at very high pressures. Unfortunately, no elevated pressure data are available in open sources for the medium-chain 1-alkyl fluorides.…”
Section: ■ Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…This time we report experimental and interpolated data on thermophysical properties of 1-chloroheptane and 1-iodoheptane at 216.08 ≤ T ≤ 423.1 K and 0.1 ≤ P ≤ 196.1 MPa. The current analysis covers also the previously published results for 1-iodohexane, 4 1chlorohexane, 5 and 1-chloropropane 6 in similar P−T ranges, along with the volumetric properties of 1-alkyl bromides 7,8 and the eminent 9 data 10−13 of Percy Williams Bridgman at very high pressures. Unfortunately, no elevated pressure data are available in open sources for the medium-chain 1-alkyl fluorides.…”
Section: ■ Introductionsupporting
confidence: 60%
“…These procedures have been described in great detail in previous studies. 4,5 The highest temperature limit of measurements was defined by the boundary of a thermal stability of the substances around 413.15−423.15 K. The results are displayed in Tables S2 and S3.…”
Section: ■ Experimental Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bolotnikov et al [45][46][47][48] and Hasanov et al 49,50 reported the u(T,P) for mainly liquid n-alkanes. Daridon and colleagues 51-68 have measured u(T,P), for ethers, esters and n-alkanes.…”
Section: Speed Of Sound In Liquid Organic Compoundsmentioning
confidence: 99%